LEVEL OF SERVICE ANALYSIS OF PEDESTRIAN FACILITY IN SPORTS COMMUNITY AREA MAJALENGKA-WEST JAVA - Galuh Kharisma; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2024)
The location has many pedestrians, such as recreational areas, and encompasses various activities ranging from commerce to sports. This research aims to understand the perceptions or voices of pedestrians, particularly visitors to Gelanggang Generasi Muda Majalengka. The research methodology is quantitative, utilizing a questionnaire that gathered responses from 50 residents of Kabupaten Majalengka who have frequently engaged in activities and visited Gelanggang Generasi Muda (GGM) Majalengka. The questionnaire data was filled out by 50 respondents exhibiting diverse characteristics, with the majority being students residing in Majalengka. The comparison of the importance and performance levels reveals a minimal GAP, which can be considered insignificant, demonstrating respondents' satisfaction with pedestrian support facilities. Based on the results from the Importance Performance Analysis (IPA) method graph, it can be concluded that two facilities, Stop Facilities (A8), Cleanliness and Trash Facilities (A6), and Disability Facilities (A9), require priority attention for improvement.